Gross Job Flows in Russian Industry Before and After Reforms: Has Destruction Become More Creative? - J. David Brown; John S. Earle (Institute for the Study of Labor (IZA), 2001)
This paper uses 1985-1999 manufacturing census data for old Russian enterprises to calculate the magnitude and productivity effects of gross job flow rates before and after reforms. Job creation was low throughout the period in this sector, but increased slightly during the transition, while job destruction rose markedly. Heterogeneity in firm employment change also increased significantly. Intra- and inter-sectoral job reallocation had no effect on aggregate labor productivity during the socialist period, while they have made a strong positive contribution during the transition. Privatization and product market competition have not led to greater job destruction overall, but rather have helped to focus the destruction in the firms with the lowest productivity.
Keywords: E24; J63; O47; P23; 330; Job destruction; job reallocation; productivity; transition; Russia; Arbeitsmobilität; Systemtransformation; Wirtschaftsreform; Industrie; Russland